CENSORSHIP, PSYCHOLOGICAL REACTANCE AND CREATIVITY: FIVE COMMUNICATION STRATEGIES FOR DESIGNING COMMUNITY GUIDELINES - Qinqin Liu (Journal of Human Development and Communication (JoHDeC), 2025)
This study explores how to design community guidelines by reducing the audience’s psychological reactance in order to build a polite and secure online community as well as to promote the community creativity. The study first explains why we need community guidelines, as an explicit and formal form of censorship. Then censorship is defined to prove that community guidelines in nature are an essential construct of society that cannot be categorized simply as a destructive or repressive force. After that, psychological reactance theory is introduced in relation to censorship and the framing of creativity is clarified in order to make the statement that it is the psychological reactance elicited by censorship that could hinder creativity, not censorship itself. Because of the negative effects brought by psychological reactance to creativity, five specific communication strategies are proposed to offer practical advice on how to make an online community more creative through the way censorship is presented: (1) reduce the use of high-controlling language; (2) add restoration postscripts; (3) increase message novelty; (4) include narrative; (5) improve clarity of request. In addition, limitations of this project are illustrated and suggestions for further validating and improving the strategies are discussed.